2012
DOI: 10.1007/s00412-012-0364-y
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation or non-reactivation: what accounts better for the silence of sex chromosomes during mammalian male meiosis?

Abstract: During the first meiotic prophase in male mammals, sex chromosomes undergo a program of transcriptional silencing called meiotic sex chromosome inactivation (MSCI). MSCI is triggered by accumulation of proteins like BRCA1, ATR, and γH2AX on unsynapsed chromosomes, followed by local changes on the sex chromatin, including histone modifications, incorporation of specific histone variants, non-histone proteins, and RNAs. It is generally thought that MSCI represents the transition of unsynapsed chromatin from a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
139
7
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(167 citation statements)
references
References 82 publications
19
139
7
2
Order By: Relevance
“…RNAs to the sex body (Page et al, 2012). However, an alternative possibility recently proposed assumes that MSCI represents the maintenance of a prior repressed state (Page et al, 2012).…”
Section: Smc5/6 Complexes At the Sex Bodymentioning
confidence: 99%
“…RNAs to the sex body (Page et al, 2012). However, an alternative possibility recently proposed assumes that MSCI represents the maintenance of a prior repressed state (Page et al, 2012).…”
Section: Smc5/6 Complexes At the Sex Bodymentioning
confidence: 99%
“…In mammals, the phosphorylated form of histone H2AX (gH2AX) is one of the characteristic responses to this damage, and thus it is used as a common marker of DNA damage during meiosis (Mahadevaiah et al 2001). Additionally, gH2AX is accumulated on sex chromosomes from pachytene up to metaphase I, where it functions in the meiotic silencing of sex chromosomes (Mahadevaiah et al 2001;Turner et al 2004;Page et al 2012).We followed the location of gH2AX during pachytene in combination with labeling of the centromeres to ascertain if the centromeres were specifically marked for DNA damage and repair during these stages (Figure 6, A-D). We found that during early pachytene gH2AX was abundantly distributed on the sex chromosomes, which showed a fuzzy appearance ( Figure 6A).…”
Section: Dna Damage-response Proteins Do Not Specifically Associate Wmentioning
confidence: 99%
“…It is then possible that the particular dynamics that RAP1 and TRF1 exhibit during prophase I could be related to protection and integrity maintenance of the ITSs, especially from pachytene up to diplotene, when chromatin in autosomes becomes decondensed and transcriptionally active (Page et al 2012). This becomes particularly important since meiosis is a critical process for genome stability.…”
Section: Structural Organization Of Its Chromatin During Meiosismentioning
confidence: 99%
“…This post-translational modification of histone H2AX is believed to trigger a positive feedback loop between H2AX and MDC1 to promote the additional recruitment of epigenetic factors responsible for silencing the sex chromosomes during meiosis (FernandezCapetillo et al, 2003;Ichijima et al, 2011). It has been reported that molecular events leading to MSCI are initiated at the zygotene to pachytene transition during prophase I in spermatocytes, and that the actual gene silencing effects are first manifest at the early pachytene stage (Page et al, 2012;Royo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%